2013
DOI: 10.1007/s00264-013-2101-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior cervical fusion by titanium mesh cage versus nano-hydroxyapatite/polyamide cage following single-level corpectomy

Abstract: Purpose The titanium mesh cage (TMC) is a typical metal cage device which has been widely used in cervical reconstruction for decades. Nano-hydroxyapatite/polyamide-66 (n-HA/PA66) cage is a novel biomimetic non-metal cage device growing in popularity in many medical centres in recent years. There has been no comparison of the efficacy between these two anterior reconstructing cages. The purpose of this study was to compare the radiographic and clinical outcomes of these two different devices. Methods Sixty-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 23 publications
(44 reference statements)
6
62
1
Order By: Relevance
“…However, the elastic modulus of the n-HA/PA66 cage was founded to be 4.0 GPa, which is substantially lower than that of a bone graft. Theoretically, the n-HA/PA66 strut can avoid the stress shield caused by some metallic implants and promote bony fusion1516. Previous studies reported satisfactory clinical and radiographic outcomes of ACCF with the n-HA/PA66 strut in short- and mid-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the elastic modulus of the n-HA/PA66 cage was founded to be 4.0 GPa, which is substantially lower than that of a bone graft. Theoretically, the n-HA/PA66 strut can avoid the stress shield caused by some metallic implants and promote bony fusion1516. Previous studies reported satisfactory clinical and radiographic outcomes of ACCF with the n-HA/PA66 strut in short- and mid-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-hydroxyapatite/polyamide66 (n-HA/PA66) is a biomimetic composite synthesized from nano-scale HA and the polar polymer PA66 and has been approved for clinical application in recent years. The n-HA/PA66 struts have been used for anterior cervical reconstruction for several years, and satisfactory clinical outcomes have been reported in previous studies141516. However, studies evaluating the long-term results of the n-HA/PA66 strut for ACCF are relatively scarce.…”
mentioning
confidence: 99%
“…A previous study showed that four years after implantation, nHA/PA66 implants directly connected with bone tissue without the immunological rejection and trabecular bone resorption caused by the stress-shielding effect. 18 The successful application of nHA/PA66 composites in the abovementioned area encouraged us to explore a broader range of their possible applications. Although the nHA/ PA66 composites have improved mechanical properties compared to PLA, our previous studies revealed that the mechanical strength of nHA/PA66 composites is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…n-HA/PA66 composites have good biocompatibility and desirable mechanical properties, and have been used successfully as scaffolds in orthopedics. 13,14,19,22,23 However, n-HA/PA66 composites cannot provide adequate mechanical strength as bone plates for fixation of fractures. In the present study, to enhance the strength of these composites, we added 30 wt% glass fibers to n-HA/PA66 when fabricating the bone plate.…”
Section: Discussionmentioning
confidence: 99%